Research on the Measurement of New Urbanization Level in Anhui Province from the Green Perspective. Issue 1 (November 2020) - Sheng, Jia; He, Xiaoyu; Qiu, Yingying; Miao, Chuanqi
Abstract: With the continuous deepening of the new urbanization process, some contradictions in its development process become increasingly obvious, among which the environmental problems are particularly prominent. People's demands for green residential towns are further raised, and the concepts of ecological city, green town and sustainable development society are put forward. In this paper, new urbanization and "green" are linked to determine the concept and connotation of green new urbanization. Under the core connotation of the green perspective, the level of new urbanization in Anhui Province is analyzed from four levels of green economy, green environment, green living and green foundation, thus promote the healthy and benign development of new urbanization and provide an opportunity to improve the mechanism of regional ecological coordinated development.